Effects of inlet velocity profiles of hybrid nanofluid flow on mixed convection through a backward facing step channel under partial magnetic field - Geridonmez, B. Pekmen; Öztop, Hakan Fehmi (Elsevier, 2021)
In this paper, mixed convection flow of a hybrid nanofluid is numerically studied in a backward facing step channel in the presence of a uniform partial magnetic field. Four different inlet velocity profiles are also taken into account. Stream function-vorticity formulation of governing dimensionless equations is adopted. The radial basis function pseudo spectral method for spatial derivatives and the backward-Euler method for time derivatives are implemented on nonuniform grids for numerical simulation of the problem. The influence of Hartmann number (between 0 and 50), Richardson number (between 0.01 and 100), the center of partial magnetic field (between 1 and 3) and the solid nanoparticle concentrations (between 0.01 and 0.04) are numerically examined. The results reveal that the smallest convective heat transfer is achieved in the step-centered partial magnetic field. The increase in magnetite nanoparticles has a significant influence on convective heat transfer, particularly, in case of sinusoidal velocity profile.
Keywords: Partial magnetic field; Mixed convection; Radial basis functions; Hybrid nanofluid; Backward facing step